ANALISIS DAMPAK KETERLAMBATAN PENGEMBALIAN REKAM MEDIS PASIEN RAWAT INAP TERHADAP PROSES ASSEMBLING, KODING, FILLING DAN PELAPORAN DI RUMAH SAKIT UMUM DHARMA YADNYA DENPASAR - Adelheid Nija (Health Care Media, 2024)
The return of inpatient medical records in accordance with Standard Operating Procedures at Dharma Yadnya General Hospital Denpasar, which must be returned no later than 1x24 hours after the patient is discharged. Based on research data in January-March 2023, the late return of inpatient medical records in the assembling section amounted to 66 (10.4%), in the coding section 68 (10.7%), in the filling section 67 (10.5%) and in the reporting section 78 (11.8%) of a total of 633 medical records. The purpose of the study was to determine the impact of delays in returning inpatient medical records on the assembling, coding, filling and reporting processes at Dharma Yadnya General Hospital, Denpasar. The research design used was descriptive qualitative analytic research with a cross-sectional approach. Respondents in this study amounted to 5 people, namely 1 head of medical records, 1 assembling officer, 1 coding officer, 1 filling officer and 1 reporting officer. Data collection methods are interviews, observation, documentation and check lists. The results showed that the impact of delays in returning medical records in the assembling section was hampered by the process of reorganizing and assembling medical records. In the coding section, the coding process is hampered due to delays and incomplete medical record content. In the filling section, the accumulation of medical record documents on the work table and the obstruction of the medical record storage process. In the Reporting section, the data collection process is hampered because the information needed to be retrieved and analyzed is incomplete and late. The study can be concluded that the delay in the return of inpatient medical records has an impact on the process of assembling, coding, filling, reporting and every month the percentage of data on the delay in returning medical records has increased.